The Effect of Concentration and Some Types of Auxins on Orchid (Dendrobium sp) Rooting Induction In-Vitro - Arnilan, Widya; Mardaleni, Mardaleni (Jurnal Agroteknologi, Agribisnis, dan Akuakultur, 2026)
The purpose of this study was to determine the effect of the interaction of concentrations and several types of auxins on the in-vitro induction of orchid plant roots. This research was carried out at the Biotechnology Laboratory of the Faculty of Agriculture, Islamic University of Riau. This research was conducted for 3 months starting from December 2022 to February 2023. This study used a RAL Split Plot Design, which consisted of the main plot, namely the type of auxins and the subplots, namely the auxin concentration of 0, 0.5, 1, and 1.5 ppm. Parameters observed were: percentage of living explants, age at which roots appeared, number of roots per explant, longest root length and percentage of explants forming roots. The research data were analyzed statistically and continued with the 5% HSD test. The results showed that the interaction effect of concentration and several types of auxins significantly affected the age of root emergence and the longest root length of Dendrobium sp. The main effect of several types of real auxin on the number of roots and the percentage of forming roots of Dendrobium sp. orchid plants, the type of auxin is NAA. The main effect of the concentration of several types of auxins is significant on the age of emergence of roots, the number of roots, the length of the longest roots and the percentage of forming roots, at the best concentration of 0.5 ppm.